SCALING OUT COMMUNITY-BASED INTEGRATED FARMING PROGRAM IN SORONG REGENCY SOUTHWEST PAPUA INDONESIA - Putra, Njo Fransiscus XaveriusAnditya Ciptadi; Ramadhan, Muhammad Ishlah; Saribanon, Nonon (Universitas Nasional, 2024)
The Integrated Farming Program was implemented in Kampung Adat Malasigi, Klayili District, as an extension of a similar initiative in Klasafet District, Southwest Papua. This program, part of the Corporate Social Responsibility (CSR) initiative by PT Pertamina EP Papua Field, in collaboration with the Kasuari Foundation and the local business institution of Sumur Olie Village, aims to boost agricultural productivity and promote processed banana products. This study examines the program's impact on local economic and social conditions. Key findings include an 80% increase in banana productivity in Kampung Adat Malasigi and a 30% increase in Klasafet District. Additionally, community income rose by 33% in Kampung Adat Malasigi and 25% in Klasafet District. The development of processed banana products, such as banana chips and dried bananas, has become a popular venture. However, challenges remain in addressing infrastructure gaps and improving market access. The study concludes that while the program has achieved notable success, further efforts in infrastructure development, institutional capacity building, and product innovation are needed to ensure long-term sustainability.